ANALISIS PENGARUH DESENTRALISASI FISKAL DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KEMISKINAN PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TIMUR TAHUN 2015-2019 - Ariel Faza Mahendra; Bahtiar Fitanto (Journal of Development Economic and Social Studies, 2024)
This study aims to determine the effect of Fiscal Decentralization on Poverty in the Regency / City of East Java Province. The study also examines the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), Revenue Sharing Fund (DBH) and Special Allocation Fund (DAK) and Gross Regional Domestic Product (GRDP) on Poverty in the Regency / City of East Java Province in 2015-2019. The data used comes from the budget realization report of the Regency / City of East Java Province published by the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency (BPS). This type of research is descriptive quantitative. Data analysis uses panel data regression analysis which is a combination of 2015-2019 time series data and crosssection data of 35 districts / cities in East Java Province. The results showed that Revenue Sharing Fund (DBH) and Gross Regional Domestic Product (GRDP) had a negative effect on poverty, then Regional Original Revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) had no effect on poverty.